The seventh plague [compact disc, unabridged] - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel, 2016)
When a British archaeologist who had been missing for two years reappears, frantic and delirious, but dies before he can tell his story, Sigma Force must stop an ancient plague with ties to some of history's most innovative minds.